The implications of physical education and sports lessons on the social value of fidelity and honesty for middle school pupils from the viewpoint of physical education and sports professors in Blida province. - kamli, Mourad (sports creativity, 2025)
This study aims to know the impact of physical education and sports lessons on the social value of fidelity and honesty for middle school pupils from the viewpoint of physical education and sports professors. This study was on middle schools for the state of Blida. For this purpose, we used the descriptive and analytical method on a sample of 50 professors who were intentionally chosen, and to collect data we used the questionnaire tool, The researcher also used each of the following statistical methods: arithmetic mean, validity of internal consistency, frequencies and percentages, Cronbach's alpha test, spss program, After collecting the results and treating them statistically, it was concluded that there are reflections of the lessons of physical education and sports on the value of fidelity and honesty among middle schoolers from the viewpoint of teachers of physical education and sports